12/{3 + sqr[5] + 2sqr[2]}
Let x = sqr[5] + 2sqr[2]
12/{3 + a} = 12(3-a)/[(3+a)(3-a)] = 12(3-a)/(9-a^2)
a^2 = (sqr[5]+2sqr[2])^2 = (sqr[5])^2 + 4 sqr[5]sqr[2] + 4(sqr[2])^2
= 5 + 4sqr[5]sqr[2] + 4(2) = 13 + [5^(1/2)][2^(1/2)] = 13+sqr[10]
Now the original becomes
12(3-x)/(13+sqr[10]) = 12(3-x)(13-sqr[10])/(13+sqr[10])(13-sqr[10])
= 12(3-x)(13-sqr[10])/(13^2 - 10)
Now do the rest. I hope that I have not made a trivial error
2007-02-28 05:43:05
·
answer #1
·
answered by kellenraid 6
·
0⤊
1⤋
Using google calculator - just search for the equation:
12/( 3+sqrt5+2*sqrt2)
gives
12 / (3 + sqrt(5) + (2 * sqrt(2))) = 1.48800388
2007-02-28 08:19:14
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
Multiply both numerator and denominator by 3sqrt5 - 2sqrt2 and the roots will disappear from the denominator after some algebra and using the relation (a - b)(a + b) = a^2 - b^2
2007-02-28 05:34:21
·
answer #3
·
answered by physicist 4
·
0⤊
1⤋
12/( 3\/5+2\/2) =
Properties of radicals:
12( 3\/5-2\/2) / ( 3\/5+2\/2)( 3\/5-2\/2) =
36\/5 - 24\/2 / 3²\/5² - 2²\/2² =
36\/5 - 24\/2 / 9.5 - 4.2 =
36\/5 - 24\/2 / 45 - 8 =
(36\/5 - 24\/2) divided by 37
><
2007-03-03 01:13:51
·
answer #4
·
answered by aeiou 7
·
0⤊
0⤋
y do u ask all ur homework on neteveryday.first try urself and if u r not able to get ans then ask. otherwise u will know nothing in exams and will get fail.u r urself losing by doing that . others who help r getting better and still gaining .dont mind and take my advise .
A WELL WISHER..............
2007-03-01 04:25:18
·
answer #5
·
answered by Diksha A 3
·
0⤊
1⤋
answer is 0. not ask such easy questions .ok? ask very difficult questions. iam sooooooooo clever , so try to defeat me .thanks daaaaaaaaaaaaa
2007-02-28 05:39:58
·
answer #6
·
answered by chiduhere 1
·
0⤊
2⤋
YES
2007-03-04 00:27:09
·
answer #7
·
answered by ratish sachdeva 1
·
0⤊
0⤋
1.488
2007-02-28 08:12:06
·
answer #8
·
answered by J.L. S 3
·
0⤊
1⤋